PsycEXTRA Dataset 1966
DOI: 10.1037/e438012004-001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contact cues on the perception of the oculogravic illusion.

Abstract: SUMMARY PAGE THE PROBLEMThe purpose of this experiment was to study the influence of otolith and nonotolith information in the perception of the visual horizontal during rotation. Five normal men and five men with defective labyrinthine function acted as observers. All measurements were made in a room which could be rotated. Initial, static measurements were made while the men stood erect in the stationary room. Similar measurements were made during rotation while the observer stood on a platform set to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is well-known that SV is not only influenced by the visual frame, but also by body tilt (Scho« ne 1964) and by modifications of the gravitational field (Clark and Graybiel 1968). This clearly suggests that all the reference frames mentioned above are potentially involved in the perceptual elaboration of the SV.…”
Section: The Subjective Vertical As the Results Of A Combination Betwementioning
confidence: 86%
“…It is well-known that SV is not only influenced by the visual frame, but also by body tilt (Scho« ne 1964) and by modifications of the gravitational field (Clark and Graybiel 1968). This clearly suggests that all the reference frames mentioned above are potentially involved in the perceptual elaboration of the SV.…”
Section: The Subjective Vertical As the Results Of A Combination Betwementioning
confidence: 86%
“…It is well known that tilt and linear acceleration are ambiguous in the absence of semicircular canal input (Clark and Graybiel 1968; Seidman et al 1998; Carriot et al 2006) as linear acceleration can represent either tilt or translation (Guedry 1974). It has been shown that high frequency acceleration is usually interpreted as translation while lower frequency acceleration is interpreted as tilt (Paige and Tomko 1991) even when semicircular canal stimulation is absent (Graybiel et al 1979; Seidman et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis would account for the lower than expected errors in subjective vertical (SV), that are induced not only by alteration of various FORs, e.g., tilt of the visual frame [27], [37], [53], but also by body tilt [54], modifications of the gravitational field [55] or even the alteration of trunk mass distribution [1]. With this view, and in line with the present results, SHO is neither perfectly lined up with the egocentric FOR, nor with the visual FOR.…”
Section: Discussionmentioning
confidence: 99%